O4. Monte Carlo modelling of a prototype beam delivery check system for intensity modulated radiation therapy plan. (September 2016) - Oderinde, O.; du Plessis, F.
Abstract : Introduction: Monte Carlo (MC) simulation techniques can accurately solve complex radiation transport challenges. This study applied the BEAMnrc Monte Carlo code technique to model an online dose monitoring system, the Integral Quality Monitoring (IQM) device (iRT Systems GmbH, Koblenz, Germany) and study the signal response of an IMRT treatment plan using the IQM model. IMRT treatments have generated complexities in their pretreatment quality assurance (QA) and there is huge curiosity to verify the treatment plan data during the real-time treatment. The Integral Quality Monitor (IQM) is an independent real-time treatment verification system which verifies the integrity and validates the accuracy of the treatment plan data. The IQM also functions as a pretreatment quality assurance tool for radiotherapy. Materials and methods: The EGSnrc/BEAMnrc MC codes were utilized to model the Elekta Synergy linac equipped with Agility 160-leaf MLC as well as a MC model of the IQM. Full clinical IMRT plans were extracted from a DICOM plan file to create input files for the MC simulations. The simulated output signals from the IQM model were generated. Results: IQM model was successfully developed and the Monte Carlo calculated IMRT signals show a good response from one segment to another of maximum IMRT plan signal. Conclusion: Application of MC techniques to online dose monitoring is authentic. It demonstrates that MC radiation transport method is virtually unlimited when it comes to solving radiation transport and dose calculation challenges.